Effects of foliar application of chemical agents and shading levels on growth and physiological aspects of malagueta pepper plants - de Araújo Ascoli, Alexandre [UNESP]; da Silva Binotti, Flávio Ferreira; de Mendonça, Gabriel Wanderley [UNESP]; Gouveia, Geraldo Candido Cabral [UNESP]; Costa, Edilson; Cardoso, Eliana Duarte (Southern Cross Publishing, 2020)
Foliar application of chemical agents and cultivation in different levels of shading can modify pepper plants. The objective of this study was to evaluate the effect of the application of chemical agents in the growth, partition of photoassimilates and photosynthetic pigments of malagueta pepper in different growing environments. The treatments were arranged in a randomized design with a 2x5 factorial scheme under two cultivation environments [eucalyptus structures measuring 5.0 x 5.0 x 2.5 m (length x width x height), coated with type coverage screens (Sombrite®) with 18% and 35% shading], and five treatments with chemical agents [1 - C - without application; 2 - PBZ (50 mg L-1 ) + Nut. (1%); 3 - Gib. (50 mg L-1 ) + Nut. (1%); 4 - Amin. (50 mg L-1 ) + Ant. (50 mg L-1 ) and 5 - Gib. (50 mg L-1 ) + A (50 mg L-1 ) + Amin. (50 mg L-1 ) + Ant. (50 mg L-1 )] in four replications. We evaluated the stem diameter, the plant height, number of leaves, leaf dimensions, leaf area, accumulation and dry matter partition and chlorophyll contents. The cultivation of pepper plants in environment with 18% of shading provides plants with a higher number of leaves and dry matter, as environment protects plants against climatic agents by controlling temperature, humidity and solar radiation. The application of the Paclobutrazol + Nitrogen promotes shoot growth and increases the green pigmentation in pepper plants.
Keywords: Capsicum frutescens L.; light incidence; partition of photoassimilates; photosynthetic pigments; protected environments